A modest proposal: Free will is real. Issue 2 (4th March 2022) - Sheldon, Kennon M.; Martela, Frank
ABSTRACT: We present a hybrid philosophical/psychological argument in defense of 'free will.' The argument builds on the proposals in philosopher Christian List'sbook, Free will is real . We show that List's psychological account of free will – that it requires the ability to consider alternatives, to make a choice, and to enact that choice – has already been proven, via research into goal functioning. Thus, the real question is: 'can we use our free will wisely ?' Self-concordance research and implicit/explicit motive discrepancy research suggest that sometimes, we can't. Ironically, the same fact that makes us free – that our choices are based on our imaginative capacities – also makes us free to be clueless, i.e., out of touch with ourselves or with reality. In building our argument we also discuss self-determination theory, the evolved symbolic self, system 1 versus system 2 functioning, and the hierarchical organization of human existence.